Rising Cesarean Section Rate, Need to Revisit Cesarean Section Indications - Sumaira Fatima Sabir, Faiqa Saleem Baig, Zahra Safdar, Sumera Zeb, Farheen Tariq, Kulsoom Shehzadi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pakistan is one of those countries where cesarean sections rate has increased unusually in the past two decades from 27% to 37.7%. Objective: This study will help to analyze the CS rate in a tertiary care center in Pakistan over a period of one year. And help to recognize the main indications for increase trend. And will help to develop strategies to decrease this ongoing increasing rate of CS. Study design: Retrospective Descriptive Study Place of study: Lahore General Hospital, Lahore Duration: one year 01-01-2021 to 31-12-2021 Methodology: This Retrospective Descriptive Study is carried out in gynecology unit 2 of Lahore General Hospital Lahore. Records of all patients who delivered in gynecology unit two over a period of one year from 1st January 2021 to 31st December 2021 are collected and analyzed. The demographic details of all the women including their age, gravidity as well as indication for CS are recorded. Results are calculated in terms of frequencies and percentages. The data is shown in forms of tables and charts. The data of the last month is plotted according to new CS classification of WHO Robson’s classification system. This will help to identify the different groups of women undergoing CS and will also identify the group with most Cesarean Sections. Results: The overall CS rate was 48.98%. In the last month Robson classification app is used and results shown in form of a table which shows the group of women with cesarean section rate. This will help to plan interventions to decrease CS rate. Conclusion: CS rate is increased overall globally, which has been seen in Pakistan also. There should be good antenatal care and one to one intrapartum care so maximum number of women delivering vaginally hence, will decrease overall CS rate and indirectly decreasing complications of CS and repeat CS especially blood transfusions & morbid adherent placenta.